Sustainability Analysis of Coffee Agribusiness in Indonesia: Environmental, Economic, and Social Perspectives - Philip Yudha Gabriel; Mitra Musika Lubis (Universitas Muhammadiyah Palu, 2025)
Sustainable coffee agribusiness is an approach to coffee cultivation, processing, and marketing that considers environmental, economic, and social aspects. This research aims to assess the sustainability of coffee agribusiness by focusing on these three aspects to ensure the coffee industry continues to grow without damaging the ecosystem, improving farmers' welfare, and strengthening economic stability. The research method used is literature review by collecting data from relevant journals, scientific articles, and previous research in the last five years. The results showed that the environmental aspects of coffee agribusiness can be maintained through the implementation of agroforestry systems, reduced use of hazardous chemicals, and better waste management. From an economic perspective, the main challenges faced by farmers are fluctuating coffee prices and high production costs. Solutions include strengthening cooperatives, diversifying processed coffee products, and accessing fair trade certification schemes. Meanwhile, the social aspects of coffee agribusiness sustainability include farmer welfare, women's empowerment, and increased involvement of the younger generation in the sector. Support from the government, private sector, and non-governmental organizations is needed to create policies that support the sustainability of coffee agribusiness. By applying the principles of sustainable agriculture, the coffee agribusiness